Observation and Feedback in Walkthrough Visits: Traditional vs. Distance Supervision Settings - Allison Rothwell; Twyla Sprouse (The Advocate, 2016)
During student teaching, many on-site university supervisors implement quick observations in order to gather more informal data about the classrooms in which they observe and better understand the role student teachers are playing at different points within the semester. While these short walkthrough observations are effective at the beginning of the semester, the data quickly becomes unbalanced between student teachers, and supervisors often have to begin scheduling the visits in order to collect more specific, balanced information. This article examines the effectiveness of the onsite walkthrough when compared to video walkthrough observations implemented within a distance supervision model.